Over-Expression of GUSB Leads to Primary Resistance of Anti-PD1 Therapy in Hepatocellular Carcinoma - Kong, Xiangyi; Zheng, Zhiying; Song, Guoxin; Zhang, Zihao; Liu, Hanyuan; Kang, Junwei; Sun, Guoqiang; Sun, Guangshun; Huang, Tian; Li, Xiao; Rong, Dawei; Wang, Ke; et al. (Frontiers in Immunology, 2022)
Immunotherapy treatments, particularly immune checkpoint blockade, can result in benefits in clinical settings. But many pre-clinical and clinical studies have shown that resistance to anti-PD1 therapy frequently occurs, leading to tumor recurrence and treatment failure, including in patients with hepatocellular carcinoma (HCC). In this study, 10 patients with HCC were remedied with anti-PD1, and pre-treatment biopsy samples were sequenced for 289 nanostring panel RNA to compare responsive and non-responsive tumors to identify possible pretreatment biomarkers or targets of anti-PD1 therapeutic responses. Fortunately, the expression of β-Glucuronidase (GUSB) in the non-responding tumors was found to be remarkably higher than that in responding tumors. Results of the cell counting kit 8 (CCK8), 5-ethynyl-2’-deoxyuridine (EdU), transwell, wound healing test, and flow cytometry showed that GUSB facilitated proliferation, invasion, as well as migration of human HCC cells and downregulated PD-L1 expression by promoting miR-513a-5p. Additionally, as a GUSB inhibitor, amoxapine can reduce the progression of human HCC cells, and was an effective treatment for HCC and improved the sensitivity of anti-PD1 therapy. In summary, this study reveals that increased GUSB downregulates PD-L1 expression by promoting miR-513a-5p, leading to primary resistance to anti-PD1 treatment in HCC, and amoxapine enhances the sensitivity of anti-PD1 therapy by inhibiting GUSB, providing a new strategy and method for improving the efficacy of anti-PD1 therapy and bringing new prospects for therapy of HCC.